Otic Neurogenesis in Xenopus laevis: Proliferation, Differentiation, and the Role of Eya1 - Suad Hamdan Almasoudi; Gerhard Schlosser (Frontiers Media S.A., 2021)
Using immunostaining and confocal microscopy, we here provide the first detailed description of otic neurogenesis in Xenopus laevis. We show that the otic vesicle comprises a pseudostratified epithelium with apicobasal polarity (apical enrichment of Par3, aPKC, phosphorylated Myosin light chain, N-cadherin) and interkinetic nuclear migration (apical localization of mitotic, pH3-positive cells). A Sox3-immunopositive neurosensory area in the ventromedial otic vesicle gives rise to neuroblasts, which delaminate through breaches in the basal lamina between stages 26/27 and 39. Delaminated cells congregate to form the vestibulocochlear ganglion, whose peripheral cells continue to proliferate (as judged by EdU incorporation), while central cells differentiate into Islet1/2-immunopositive neurons from stage 29 on and send out neurites at stage 31. The central part of the neurosensory area retains Sox3 but stops proliferating from stage 33, forming the first sensory areas (utricular/saccular maculae). The phosphatase and transcriptional coactivator Eya1 has previously been shown to play a central role for otic neurogenesis but the underlying mechanism is poorly understood. Using an antibody specifically raised against Xenopus Eya1, we characterize the subcellular localization of Eya1 proteins, their levels of expression as well as their distribution in relation to progenitor and neuronal differentiation markers during otic neurogenesis. We show that Eya1 protein localizes to both nuclei and cytoplasm in the otic epithelium, with levels of nuclear Eya1 declining in differentiating (Islet1/2+) vestibulocochlear ganglion neurons and in the developing sensory areas. Morpholino-based knockdown of Eya1 leads to reduction of proliferating, Sox3- and Islet1/2-immunopositive cells, redistribution of cell polarity proteins and loss of N-cadherin suggesting that Eya1 is required for maintenance of epithelial cells with apicobasal polarity, progenitor proliferation and neuronal differentiation during otic neurogenesis.